Effect of Anodic Mass Transfer in the Electrowinning of Copper in Presence of Organic Compounds - M. El-Mallah, Nabila; M. Ahmed, Abdel-Monem; F. Gado, Lamyaa (Asian Journal of Chemistry, 2012)
The effect of anodic oxygen bubbles on the rate of mass transfer was studied by measuring the limiting current of deposition of copper from acidified CuSO4 solution using parallel plate cell. Different factors studied as types of inhibitors, their concentrations and temperatures. The organic additives used are glucose, fructose, mannose, sucrose, lactose and maltose. The rate of mass transfer was found to decrease over the natural convection value by an amount ranging from 1.8-32.3 % depending on the types of additives and its concentration. Thermodynamic parameters Ea, DH*, DS*, DG* were evaluated and discussed. The adsorption of organic additives was found to obey Langmuir, Temkin, Flory-Huggin and kinetic adsorption isotherm.